E.K. Pekarsky’s dictionary of the yakut language as a kind of special supertext - Rufova, Elena Stepanovna (Revista EntreLinguas, 2021)
This article studies E.K. Pekarsky’s Dictionary of the Yakut language within the scientific problem related to a supertext. Linguistic and literary works consider supertext as a multidimensional, cross-temporal, cross-personal, and polygenre phenomenon within the framework of the interpreted integrity of a number of independent texts; and integrity as a paradigmatic component is a constitutive part of the supertext. In supertexts, the textual component forms intertextual links and is revealed in the textual concept sphere, and simultaneously forms supertext links, creating a single text space. Este artículo estudia a Diccionario de E.K. Pekarsky del lenguaje Yakut dentro del problema científico relacionado con un supertexto. Las obras lingüísticas y literarias consideran el supertexto como un fenómeno multidimensional, transtemporal, transpersonal y poligénico en el marco de la integridad interpretada de varios textos independientes; y la integridad como componente paradigmático es parte constitutiva del supertexto. En los supertextos, el componente textual forma enlaces intertextuales y se revela en la esfera del concepto textual, y simultáneamente forma enlaces de supertexto, creando un solo espacio de texto. Este artigo estuda O Dicionário de E.K. Pekarsky da língua Yakut dentro do problema científico relacionado a um supertexto. As obras linguísticas e literárias consideram o supertexto como um fenômeno multidimensional, intertemporal, interpessoal e poligênico dentro da estrutura da integridade interpretada de uma série de textos independentes; e integridade como um componente paradigmático é uma parte constitutiva do supertexto. Nos supertextos, o componente textual forma links intertextuais e é revelado na esfera do conceito textual e, simultaneamente, forma links de supertexto, criando um único espaço de texto.